The influence of aging on pathologic and immunobiologic parameters of invasive ductal breast carcinoma - Ivković-Kapicl Tatjana; Knežević-Ušaj Slavica; Panjković Milana; Ninčić Dejan; Mastilović Katarina (Vojnosanitetski Pregled)
Background/Aim. Most human cancers, including breast one, increase in frequency with aging. The aim of this study was to explore the hypothesis that aging also alters breast cancer biology. Methods. The study included 120 women with primary invasive ductal carcinoma of the breast. We correlated the patients age and diagnosis with the commonly used clinical, pathological factors and newer tumor biomarkers. Immunohistochemical staining was conducted for p53, c-erbB-2, Ki-67, estrogen (ER), progesterone (PR) receptors, and angiogenesis. Results. In our study, the patients with axillary lymph node metastases and negative steroid hormone receptors (ER and PR) were significantly younger than the patients with nodal involvement and positive hormone receptors. There was also a significant association between the patients age, diagnosis and angiogenesis. No association was found between the patients age and tumor size, histological grade, p53, c-erbB-2, and Ki-67. Conclusion. The results of our study supported only partially the hypothesis that the breast cancer biology is significantly affected by a patient's age.